In-depth characterization of N-glycosylation and sialic acid content in fetal and adult fibrinogen - Tana V. Palomino; Anastasia Sheridan; David C. Muddiman; Ashley C. Brown (Research and Practice in Thrombosis and Haemostasis, 2024)
Background: Fetal fibrinogen is a variant present in neonates. Blood products used in neonates are tailored for adults and do not seamlessly integrate into neonatal clots. Increased sialic acid content has been found in fetal fibrinogen compared with adult fibrinogen. However, the extent or location of sialic acids on fibrinogen remains unknown. Objectives: To investigate differences in glycosylation and sialic acid content between fetal and adult fibrinogen. Methods: Glycans were eluted from human cord blood-isolated fetal fibrinogen and commercially available adult fibrinogen using filter-aided N-linked glycan separation. A α, B β, and λ chains were isolated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and in-gel enzymatic digestion was performed. Infrared matrix-assisted laser desorption electrospray ionization mass spectrometry was used for analysis. Results: In total, 39 and 22 glycans were detected in fetal and adult fibrinogen, respectively. Fetal fibrinogen glycans were most abundant in the lower molecular weight range <4 kDa. After isolating the Aα, Bβ, and λ chains, increased glycosylation and sialic acid content was found in fetal fibrinogen. Increased glycosylation was detected across all 3 chains, and increased sialic acid content was found in the Bβ chain. Conclusion: Sialylation in the Bβ chain of fetal fibrinogen supports previous findings showing more knob ‘B’ interactions occur in fetal fibrinogen than in adult fibrinogen during clot polymerization. This is also the first detection of glycosylation in the Aα chain of fibrinogen. By elucidating the fibrinogen N-linked glycome, this study found where sialic acid content differs the most between adult and fetal fibrinogen. This can ultimately be used to develop blood products that are neonatal-compatible.